The benthic genus Prorocentrum (Dinophyceae) in Aotearoa New Zealand and Rangitāhua Kermadec Islands: Genetic diversity, distribution, and diarrhetic shellfish toxin profile - Tomohiro Nishimura; J. Sam Murray; Kirsty F. Smith; Lucy Thompson; Joshua Fitzgerald; Emillie Passfield; Muharrem Balci; D. Tim Harwood; Sarah Challenger; Masao Adachi; Lesley L. Rhodes (Harmful Algae, 2026)

Global Analysis of Shallow Underwater Fish Observation Research: 70 Years of Progress, Persistent Geographic Biases and a Path Forward - Angus John van Wyk; Rick D. Stuart‐Smith; Jordan S. Goetze; Eva Maire; Elodie Heyns‐Veale; Kaylee Smit; Tim J. Langlois; M. Aaron MacNeil; Alejandro Pérez‐Matus; Amanda T. Lombard; Ana Carolina; Christy Semmens; et al. (Fish and Fisheries, 2026)
Marine ecosystems are increasingly threatened by overfishing, pollution, coastal development and climate change, underscoring the need for long‐term, representative information on key fish populations and habitats to inform management and policy. Underwater fish observation (UFObs) techniques, such as Underwater Visual Census (UVC), stereo‐Baited Remote Underwater Video (stereo‐BRUV) and Remotely Operated Vehicles (ROVs), play a key role in sustaining long‐term data collection. Despite technological advancements, gaps persist in understanding research focus, geographic distribution and methodological biases inherent in these methods. We conducted a scientometric analysis of 1443 peer‐reviewed publications (1953–2023), employing natural language processing and network analysis to map the research landscape. We identified 15 knowledge clusters, including marine protected areas, apex predator conservation and reef ecosystems. Our findings reveal increasing use of BRUVS and ROVs in studies of marine protected areas and subsea infrastructure, while UVC remains prevalent in shallow coral reef research. Geographic representation is skewed, with the field dominated by researchers based in Australia and the United States, and underrepresented in Africa and Southeast Asia. This imbalance highlights the need for more inclusive, globally coordinated monitoring and reporting. Our results underscore the urgency of standardising protocols within each observation method and developing interoperable reporting frameworks across techniques to maximise data comparability and foster international collaboration. Addressing these challenges will strengthen the field's capacity to inform global conservation strategies and support sustainable fisheries management.

Adaptive management and optimisation of stream monitoring network design through an integrated monitoring and modelling approach - Vaughn Grey; Kate Smith-Miles; Belinda E. Hatt; Rhys A. Coleman; Tim D. Fletcher (Journal of Hydrology, 2026)

Ingestion of Alexandrium pacificum Cysts by a Deposit Feeder: An Option for Ecosystem‐Based Approach Benefiting Aquaculture and Coastal Communities? - Leonardo N. Zamora; Kirsty F. Smith; Jacqui Stuart; D. Tim Harwood; Shenae L. Wales; Emillie M. F. Passfield; Lincoln Mackenzie (New Zealand Journal of Marine and Freshwater Research, 2026)
Harmful algal blooms caused by the paralytic shellfish toxin‐producing species Alexandrium pacificum have increased in recent years in one of the most important aquaculture regions of New Zealand, the Marlborough Sounds. Reoccurring blooms have created large cysts beds in the sediments throughout the sounds. In this region, large populations of the sea cucumber Australostichopus mollis can also be found. These deposit feeders potentially ingest the resting cysts of A. pacificum when feeding. To investigate this, we used molecular techniques to evaluate and quantify cyst ingestion, and chemical analysis to determine toxin accumulation in A. mollis . Results indicate that sea cucumbers can act as bioindicators of cyst distribution through their selective feeding behaviours, with high concentrations of A. pacificum DNA in foregut samples. Sea cucumbers could also serve as a biocontrol tool, as A. pacificum DNA concentrations decreased along the digestive tract, from the foregut to the hindgut, indicating a reduction in cyst number during the digestion process. Furthermore, no toxin accumulation was detected in the sea cucumber tissue. These encouraging results open the possibility for further research to evaluate the efficiency of integrated biocontrol management and the emergence of a multi‐impact aquaculture sector around this iconic New Zealand echinoderm.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Harnessing the strengths of machine learning and geostatistics to improve streamflow prediction in ungauged basins; the best of both worlds - Vaughn Grey; Tim D. Fletcher; Kate Smith-Miles; Belinda E. Hatt; Rhys A. Coleman (Journal of Hydrology, 2025)

High ciguatoxin-producing Gambierdiscus clade (Gonyaulacales, Dinophyceae) as a source of toxins causing ciguatera poisoning - Shauna A. Murray; Arjun Verma; Mona Hoppenrath; D. Tim Harwood; J. Sam Murray; Kirsty F. Smith; Richard Lewis; Sarah C. Finch; Shikder Saiful Islam; Amna Ashfaq; Caroline Dornelles De Azevedo; Christopher J.S. Bolch (Science of The Total Environment, 2025)

The Utility of Fish Population Monitoring and Forecast Trigger Development for Designing Adaptive Aquatic Monitoring Plans for Large Industrial Developments - Carolyn JM Brown; Tim J. Arciszewski; R. Allen Curry; D. Scott Smith; Kelly R. Munkittrick (Environmental Management, 2025)

Cross‐Continental Analysis Shows That Disturbance Effects on Reptile Body Condition Do Not Predict Abundance Responses - Kristina J. Macdonald; Don A. Driscoll; Michael D. Craig; Robert A. Davis; Steven J. Hromada; C. M. Gienger; Lee A. Fitzgerald; Daniel J. Leavitt; Danielle K. Walkup; Rickard Abom; Adrian F. Wayne; Gordon R. Friend; et al. (Global Change Biology, 2025)
Ecological disturbances are discrete events that alter or transform the physical, chemical, or biological characteristics of ecosystems. Disturbance can cause animal populations to decline and, according to the risk‐disturbance hypothesis and population collapse framework, these declines can be predicted by declines in animal body condition. However, no research has empirically examined the general relationship between body condition and abundance, nor their relationship in response to disturbance. We used a combined dataset representing 33 studies and > 42,000 observations of 75 species from Australia, New Zealand, Spain and the United States of America to test predictions relating to the relationship between reptile body condition and abundance. We first investigated the relationship at the site level and then used meta‐analytical models to test whether populations showed linked changes in abundance and body condition in response to disturbance. We further tested whether key environmental and species traits influenced this relationship and whether there was a time‐lagged effect of body condition responses on abundance. We found a positive relationship between mean reptile body condition and abundance at the site level. However, the relationship was largely lost when investigating population responses to disturbance. As such, our results provided no support for the risk‐disturbance hypothesis and limited support for the population collapse framework. Therefore, the impacts of disturbance on reptile body condition cannot be assumed to reflect or predict abundance responses. We provide a new conceptual framework that shows how disturbances can modify or uncouple the relationship between abundance and body condition by influencing underlying drivers, such as predation, competition and resource availability. Monitoring programs that infer population impacts based on changes in body condition should first confirm the relationship between these two variables in the relevant study system.

Engineering Performance and Spatial Models Highlight Key Considerations for Supporting Broadscale Replacement of Environmentally Sensitive (ES) Vessel Moorings - Lincoln S. Wong; Andrew Martini; Tim P. Lynch; Carlie Devine; Lauren Hardiman; Felicity R. McEnnulty; Rick D. Stuart-Smith; D. Jeff Ross (Coastal Management, 2025)

Analysis of irregularly sampled stream temperature time series: challenges and solutions - Vaughn Grey; Belinda E. Hatt; Tim D. Fletcher; Kate Smith-Miles; Rhys A. Coleman (Journal of Hydrology, 2024)

Population parameters and conservation implications for one of the world's rarest marine fishes, the red handfish ( Thymichthys politus ) - Tyson J. Bessell; Rick D. Stuart‐Smith; Olivia J. Johnson; Neville S. Barrett; Tim P. Lynch; Andrew J. Trotter; Jemina Stuart‐Smith (Journal of Fish Biology, 2024)
Population estimates are required for effective conservation of many rare marine species, but can be difficult to obtain. The critically endangered red handfish ( Thymichthys politus ) is a coastal anglerfish known only from two fragmented populations in southeast Tasmania, Australia. It is at a high risk of extinction due to low numbers, loss of habitat, and the impacts of climate change. To aid conservation efforts, we provide the first empirical population size estimates of red handfish and investigate other important aspects of the species' life history, such as growth, habitat association, and movement. We surveyed both red handfish local populations via underwater visual census on scuba over 3 years and used photographic mark‐recapture techniques to estimate biological parameters. In 2020, the local adult population size was estimated to be 94 (95% confidence interval [CI] 40–231) adults at one site, and 7 (95% CI 5–10) at the other site, suggesting an estimated global population of 101 adults. Movement of individuals was extremely limited at 48.5 m (± 77.7 S.D. ) per year. We also found evidence of declining fish density, a declining proportion of juveniles, and increasing average fish size during the study. These results provide a serious warning that red handfish are likely sliding toward extinction, and highlight the urgent need to expand efforts for ex situ captive breeding to bolster numbers in the wild and maintain captive insurance populations, and to protect vital habitat to safeguard the species' ongoing survival in the wild.

The impact of body mass index and physical disability on home-based anal self-sampling - Jenna Nitkowski; Maria E. Fernandez; Tim Ridolfi; Elizabeth Chiao; Anna R. Giuliano; Vanessa Schick; Michael D. Swartz; Jennifer S. Smith; Alan G. Nyitray (Cancer Causes & Control, 2024)

Empirical evidence of climate change and urbanization impacts on warming stream temperatures - Vaughn Grey; Kate Smith-Miles; Tim D. Fletcher; Belinda E. Hatt; Rhys A. Coleman (Water Research, 2023)

Using in-situ strain measurements to evaluate the accuracy of stress estimation procedures from fracture injection/shut-in tests - Yves Guglielmi; Mark McClure; Jeffrey Burghardt; Joseph P. Morris; Thomas Doe; Pengcheng Fu; Hunter Knox; Vince Vermeul; Tim Kneafsey; J. Ajo-Franklin; T. Baumgartner; K. Beckers; et al. (International Journal of Rock Mechanics and Mining Sciences, 2023)

Honey bee drones are synchronously hyperactive inside the nest - Louisa C. Neubauer; Jacob D. Davidson; Benjamin Wild; David M. Dormagen; Tim Landgraf; Iain D. Couzin; Michael L. Smith (Animal Behaviour, 2023)

Simulating the source waters for the Wilkins Peak Member evaporite sequence with modern soda spring analogues - William D. Arnuk; Tim K. Lowenstein; Elizabeth M. Klonowski; Alan R. Carroll; M. Elliot Smith (Applied Geochemistry, 2023)

Molecular detection and distribution of the genera Amphidoma and Azadinium (Amphidomataceae, Dinophyceae) in the coastal waters of Aotearoa/New Zealand - Muharrem Balci; Lesley L. Rhodes; Tomohiro Nishimura; J. Sam Murray; D. Tim Harwood; A. Lincoln MacKenzie; Tony Bui; Catherine Moisan; Lucy Thompson; Kirsty F. Smith (New Zealand Journal of Marine and Freshwater Research, 2023)
Molecular‐based approaches for harmful algal bloom species, which can be difficult to identify by light microscopy, are important tools for detecting and predicting the blooms. In this study, 84 samples from Aotearoa/New Zealand coastal waters that contained Azadinium ‐like cells were analysed using an Amphidomataceae real‐time PCR assay. Nineteen samples were positive, and 24 Azadinium ‐like clonal isolates were established from these samples. Subsequently, only five isolates from one sampling point were positive using the real‐time PCR assay. Four of the five isolates were genetically identified as Amphidoma languida and one as Azadinium dalianense . The field samples were analysed retrospectively using the species‐specific real‐time PCR assays; Am. languida was detected from the temperate areas, while Az. poporum and Az. spinosum were detected at one site. Two representative strains of each species were analysed by liquid chromatography‐tandem mass spectrometry (LC‐MS/MS), including Am. languida, which is known as toxic in the previous studies, but neither produced the currently monitored azaspiracids (AZAs). These two newly recorded species for New Zealand are important findings. The results highlight the need for more information on the spatio‐temporal variations of potentially toxic Amphidomataceae species and the risk of AZAs in New Zealand coastal waters.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Persistent thermally driven shift in the functional trait structure of herbivorous fishes: Evidence of top‐down control on the rebound potential of temperate seaweed forests? - Nestor E. Bosch; Matthew McLean; Salvador Zarco‐Perello; Scott Bennett; Rick D. Stuart‐Smith; Adriana Vergés; Albert Pessarrodona; Fernando Tuya; Tim Langlois; Claude Spencer; Sahira Bell; Benjamin J. Saunders; et al. (Global Change Biology, 2022)
Extreme climatic events can reshape the functional structure of ecological communities, potentially altering ecological interactions and ecosystem functioning. While these shifts have been widely documented, evidence of their persistence and potential flow‐on effects on ecosystem structure following relaxation of extreme events remains limited. Here, we investigate changes in the functional trait structure – encompassing dimensions of resource use, thermal affinity, and body size – of herbivorous fishes in a temperate reef system that experienced an extreme marine heatwave (MHW) and subsequent return to cool conditions. We quantify how changes in the trait structure modified the nature and intensity of herbivory‐related functions (macroalgae, turf, and sediment removal), and explored the potential flow‐on effects on the recovery dynamics of macroalgal foundation species. The trait structure of the herbivorous fish assemblage shifted as a result of the MHW, from dominance of cool‐water browsing species to increased evenness in the distribution of abundance among temperate and tropical guilds supporting novel herbivory roles (i.e. scraping, cropping, and sediment sucking). Despite the abundance of tropical herbivorous fishes and intensity of herbivory‐related functions declined following a period of cooling after the MHW, the underlying trait structure displayed limited recovery. Concomitantly, algal assemblages displayed a lack of recovery of the formerly dominant foundational species, the kelp Ecklonia radiata , transitioning to an alternative state dominated by turf and Sargassum spp. Our study demonstrates a legacy effect of an extreme MHW and exemplified the value of monitoring phenotypic (trait mediated) changes in the nature of core ecosystem processes to predict and adapt to the future configurations of changing reef ecosystems.

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Historical Trends of Sperm Whale (Physeter macrocephalus) Distribution in the Phoenix Archipelago - Brian R. C. Kennedy; Lara Hakam; Jan Witting; Regen Milani; Sue Taei; Tim Smith; Erin Taylor; Tooreka Teemari; Randi D. Rotjan (Frontiers in Marine Science, 2021)
The Phoenix Archipelago in the Central Pacific is situated in what was once one of the most productive areas for capturing sperm whales ( Physeter macrocephalus ). These whales were the focal targets of American offshore whalers in the mid-19th century along the equator, an area known as the “on-the-line” whaling grounds. Now, as large-scale Marine Protected Areas (MPAs) have provided protection for marine mammals and their food sources, it is important to have a solid understanding of historical baselines so recovery distributions can be compared with pre-whaling distributions. The Phoenix Islands archipelago contains two large MPAs: the Phoenix Islands Protected Area (PIPA), established by Kiribati in 2008, and the Howland/Baker unit of the Pacific Remote Islands Marine National Monument (PRIMNM), established by the United States in 2009. Using historic whaling records from American whaling vessels operated through the wider Phoenix Archipelago region, we reconstructed information about the presence and distribution of P. microcephalus throughout the 1800s within and around PIPA and the Howland/Baker units of the PRIMNM. Historical data analyzed using ArcGIS showed that sperm whales were present year-round within the study area, which is consistent with 20th century records from the Ocean Biogeographic Information System (OBIS). A Getis Ord Gi ∗ hotspot analysis also revealed sighting hotspots within PIPA and near Howland and Baker, suggesting that these two areas may be of long-term ecological importance to sperm whales in the central Pacific. The New England whaling fleet ceased whaling effort in the central Pacific in the late 1800s, and publicly available records since that time are scarce. There has been no modern systematic whale survey ever conducted within the Phoenix Archipelago, though anecdotal accounts and sightings have been compiled over the years. These intermittent accounts suggest that though whale populations have not recovered to pre-whaling baselines, large-scale MPAs may play a role in helping to foster a resurgence of marine mammal populations. As the network of large-scale MPAs continue to grow as part of the commitment to ocean conservation set forth by UNESCO, IUCN, and the UN Decade for Ocean Science, historical baselines will be critical as a “yardstick” to measure population resurgence success for each MPA, and for populations overall.

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

The interplay of landscape composition and configuration: new pathways to manage functional biodiversity and agroecosystem services across Europe - Emily A. Martin; Matteo Dainese; Yann Clough; András Báldi; Riccardo Bommarco; Vesna Gagic; Michael P.D. Garratt; Andrea Holzschuh; David Kleijn; Anikó Kovács‐Hostyánszki; Lorenzo Marini; Simon G. Potts; et al. (Ecology Letters, 2019)
Managing agricultural landscapes to support biodiversity and ecosystem services is a key aim of a sustainable agriculture. However, how the spatial arrangement of crop fields and other habitats in landscapes impacts arthropods and their functions is poorly known. Synthesising data from 49 studies (1515 landscapes) across Europe, we examined effects of landscape composition (% habitats) and configuration (edge density) on arthropods in fields and their margins, pest control, pollination and yields. Configuration effects interacted with the proportions of crop and non‐crop habitats, and species’ dietary, dispersal and overwintering traits led to contrasting responses to landscape variables. Overall, however, in landscapes with high edge density, 70% of pollinator and 44% of natural enemy species reached highest abundances and pollination and pest control improved 1.7‐ and 1.4‐fold respectively. Arable‐dominated landscapes with high edge densities achieved high yields. This suggests that enhancing edge density in European agroecosystems can promote functional biodiversity and yield‐enhancing ecosystem services.

Recent multivariate changes in the North Atlantic climate system, with a focus on 2005–2016 - Jon Robson; Rowan T. Sutton; Alex Archibald; Fenwick Cooper; Matthew Christensen; Lesley J. Gray; N. Penny Holliday; Claire Macintosh; Malcolm McMillan; Ben Moat; Maria Russo; Rachel Tilling; et al. (International Journal of Climatology, 2018)
Major changes are occurring across the North Atlantic climate system, including in the atmosphere, ocean and cryosphere, and many observed changes are unprecedented in instrumental records. As the changes in the North Atlantic directly affect the climate and air quality of the surrounding continents, it is important to fully understand how and why the changes are taking place, not least to predict how the region will change in the future. To this end, this article characterizes the recent observed changes in the North Atlantic region, especially in the period 2005–2016, across many different aspects of the system including: atmospheric circulation; atmospheric composition; clouds and aerosols; ocean circulation and properties; and the cryosphere. Recent changes include: an increase in the speed of the North Atlantic jet stream in winter; a southward shift in the North Atlantic jet stream in summer, associated with a weakening summer North Atlantic Oscillation; increases in ozone and methane; increases in net absorbed radiation in the mid‐latitude western Atlantic, linked to an increase in the abundance of high level clouds and a reduction in low level clouds; cooling of sea surface temperatures in the North Atlantic subpolar gyre, concomitant with increases in the western subtropical gyre, and a decline in the Atlantic Ocean's overturning circulation; a decline in Atlantic sector Arctic sea ice and rapid melting of the Greenland Ice Sheet. There are many interactions between these changes, but these interactions are poorly understood. This article concludes by highlighting some of the key outstanding questions.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

The dinoflagellate genera Gambierdiscus and Ostreopsis from subtropical Raoul Island and North Meyer Island, Kermadec Islands - Lesley L. Rhodes; Kirsty F. Smith; Arjun Verma; Sam Murray; D. Tim Harwood; Tom Trnski (New Zealand Journal of Marine and Freshwater Research, 2017)
An expedition to North Meyer Island, Kermadec Islands, in November 2015, resulted in the isolation of two Gambierdiscus species, G. australes and a previously unknown Gambierdiscus species maintained in the Cawthron Institute Culture Collection of Micro‐algae as CAWD242. Identifications were based on morphology and DNA sequence data analysis. Nine isolates of G. australes produced maitotoxin‐1 (MTX‐1) ranging from present (detectable but below the confidence level) to 36.6 pg per cell. One further isolate did not produce MTX‐1, but all G. australes isolates produced putative MTX‐3. Isolate CAWD242 was negative for MTX‐1 but produced MTX‐3. Ostreopsis sp. 3 isolated from samples collected during an earlier expedition in 2013 produced low concentrations of palytoxin (PLTX)‐like compounds (0.013 pg per cell), but an isolate of the same species from samples collected in 2015 was non‐toxic. Other dinoflagellates isolated and identified were Coolia malayensis , Amphidinium carterae and Prorocentrum hoffmannianum .

Car8 dorsal root ganglion expression and genetic regulation of analgesic responses are associated with a cis-eQTL in mice - Roy C. Levitt; Gerald Y. Zhuang; Yuan Kang; Diana M. Erasso; Udita Upadhyay; Mehtap Ozdemir; Eugene S. Fu; Konstantinos D. Sarantopoulos; Shad B. Smith; William Maixner; Luda Diatchenko; Eden R. Martin; et al. (Mammalian Genome, 2017)

A sperm whale's perspective: The importance of seasonality and seamount depth - Courtney H. Hann; Tim D. Smith; Leigh G. Torres (Marine Mammal Science, 2016)

A spatially explicit estimate of the prewhaling abundance of the endangered North Atlantic right whale - Sophie Monsarrat; M. Grazia Pennino; Tim D. Smith; Randall R. Reeves; Christine N. Meynard; David M. Kaplan; Ana S.L. Rodrigues (Conservation Biology, 2016)
The North Atlantic right whale (NARW) (Eubalaena glacialis) is one of the world's most threatened whales. It came close to extinction after nearly a millennium of exploitation and currently persists as a population of only approximately 500 individuals. Setting appropriate conservation targets for this species requires an understanding of its historical population size, as a baseline for measuring levels of depletion and progress toward recovery. This is made difficult by the scarcity of records over this species’ long whaling history. We sought to estimate the preexploitation population size of the North Atlantic right whale and understand how this species was distributed across its range. We used a spatially explicit data set on historical catches of North Pacific right whales (NPRWs) (Eubalaena japonica) to model the relationship between right whale relative density and the environment during the summer feeding season. Assuming the 2 right whale species select similar environments, we projected this model to the North Atlantic to predict how the relative abundance of NARWs varied across their range. We calibrated these relative abundances with estimates of the NPRW total prewhaling population size to obtain high and low estimates for the overall NARW population size prior to exploitation. The model predicted 9,075–21,328 right whales in the North Atlantic. The current NARW population is thus

Response to “Comment on ‘Seagrass Viviparous Propagules as a Potential Long-Distance Dispersal Mechanism’ by A. C. G. Thomson et al” - Alexandra C. G. Thomson; Paul H. York; Tim M. Smith; Craig D. H. Sherman; David J. Booth; Michael J. Keough; D. Jeff Ross; Peter I. Macreadie (Estuaries and Coasts, 2016)

Detection of Azadinium poporum in New Zealand: the use of molecular tools to assist with species isolations - Kirsty F. Smith; Lesley Rhodes; D. Tim Harwood; Janet Adamson; Catherine Moisan; Rex Munday; Urban Tillmann (Journal of Applied Phycology, 2016)

The cost of reproduction: differential resource specialization in female and male California sea otters - Emma A. Elliott Smith; Seth D. Newsome; James A. Estes; M. Tim Tinker (Oecologia, 2015)

The potential role of microRNAs in regulating gonadal sex differentiation in the chicken embryo - Andrew D. Cutting; Stephanie C. Bannister; Tim J. Doran; Andrew H. Sinclair; Mark V. L. Tizard; Craig A. Smith (Chromosome Research, 2012)

The integration of land and marine spatial planning - Hance D. Smith; Frank Maes; Tim A. Stojanovic; Rhoda C. Ballinger (Journal of Coastal Conservation, 2011)

Trophic level asynchrony in rates of phenological change for marine, freshwater and terrestrial environments - STEPHEN J. THACKERAY; TIMOTHY H. SPARKS; MORTEN FREDERIKSEN; SARAH BURTHE; PHILIP J. BACON; JAMES R. BELL; MARC S. BOTHAM; TOM M. BRERETON; PAUL W. BRIGHT; LAURENCE CARVALHO; TIM CLUTTON‐BROCK; ALISTAIR DAWSON; et al. (Global Change Biology, 2010)
Recent changes in the seasonal timing (phenology) of familiar biological events have been one of the most conspicuous signs of climate change. However, the lack of a standardized approach to analysing change has hampered assessment of consistency in such changes among different taxa and trophic levels and across freshwater, terrestrial and marine environments. We present a standardized assessment of 25 532 rates of phenological change for 726 UK terrestrial, freshwater and marine taxa. The majority of spring and summer events have advanced, and more rapidly than previously documented. Such consistency is indicative of shared large scale drivers. Furthermore, average rates of change have accelerated in a way that is consistent with observed warming trends. Less coherent patterns in some groups of organisms point to the agency of more local scale processes and multiple drivers. For the first time we show a broad scale signal of differential phenological change among trophic levels; across environments advances in timing were slowest for secondary consumers, thus heightening the potential risk of temporal mismatch in key trophic interactions. If current patterns and rates of phenological change are indicative of future trends, future climate warming may exacerbate trophic mismatching, further disrupting the functioning, persistence and resilience of many ecosystems and having a major impact on ecosystem services.

Historical distribution of right whales in the North Pacific - Elizabeth Josephson; Tim D Smith; Randall R Reeves (Fish and Fisheries, 2008)
Fisheries records provide some of the only information on pre‐fishing distribution and abundance for species that were depleted before the advent of modern scientific investigations. This paper interprets records of the early history of whaling for North Pacific right whales ( Eubalaena pacifica ). The current population occupies only a fraction of its historical range. Historical distributions of several whale species have been inferred from charts prepared by Matthew Fontaine Maury in the early 1850s and Charles Haskins Townsend in the 1930s based on data from American whalers’ logbooks. In the North Pacific, Maury’s chart has been interpreted to show that right whales occurred continuously across the entire basin. However, we find plotting errors when we compare the North Pacific chart to the corresponding data worksheets prepared for Maury (the ‘Maury Abstracts’) and the chart appears to have misled historians and biologists. Although these charts and those in the North Atlantic are wrong, the Maury Abstracts themselves appear largely consistent with the original whaler logbooks. Our analysis shows that right whales were likely not distributed continuously across the North Pacific, but instead had a pronounced longitudinally bimodal distribution and were encountered infrequently in the central‐northern North Pacific. This work shows how valuable information can be obtained by examining original source material. The American whaling logbooks are extensive and have been largely overlooked in studies of whale populations.

Balancing bias and precision in capture‐recapture estimates of abundance - Nancy A. Friday; Tim D. Smith; Peter T. Stevick; Judy Allen; Tom Fernald (Marine Mammal Science, 2008)
Capture‐recapture estimates of abundance using photographic identification data are sensitive to the quality of photographs used and distinctiveness of individuals in the population. Here analyses are presented for examining the effects of photographic quality and individual animal distinctiveness scores and for objectively selecting a subset of data to use for capture‐recapture analyses using humpback whale ( Megaptera novaeangliae ) data from a 2‐year study in the North Atlantic. Photographs were evaluated for their level of quality and whales for their level of individual distinctiveness. Photographic quality scores had a 0.21 probability of changing by a single‐quality level, and there were no changes by two or more levels. Individual distinctiveness scores were not independent of photographic quality scores. Estimates of abundance decreased as poor‐quality photographs were removed. An appropriate balance between precision and bias in abundance estimates was achieved by removing the lowest‐quality photographs and those of incompletely photographed flukes given our assumptions about the true population abundance. A simulation of the selection process implied that, if the estimates are negatively biased by heterogeneity, the increase in bias produced by decreasing the sample size is not more than 2%. Capture frequencies were independent of individual distinctiveness scores.

USING HISTORICAL RECORDS TO RELOCATE A LONG‐FORGOTTEN SUMMER FEEDING GROUND OF NORTH ATLANTIC RIGHT WHALES - Tim D. Smith; Klaus Barthelmess; Randall R. Reeves (Marine Mammal Science, 2006)

Autopsy your dead…and living: a proposal for fisheries science, fisheries management and fisheries - Tim D. Smith; Jason S. Link (Fish and Fisheries, 2005)
Ghoti papers Ghoti aims to serve as a forum for stimulating and pertinent ideas. Ghoti publishes succinct commentary and opinion that addresses important areas in fish and fisheries science. Ghoti contributions will be innovative and have a perspective that may lead to fresh and productive insight of concepts, issues and research agendas. All Ghoti contributions will be selected by the editors and peer reviewed. Etymology of Ghoti George Bernard Shaw (1856‐1950), polymath, playwright, Nobel prize winner, and the most prolific letter writer in history, was an advocate of English spelling reform. He was reportedly fond of pointing out its absurdities by proving that ‘fish’ could be spelt ‘ghoti’. That is: ‘gh’ as in ‘rough’, ‘o’ as in ‘women’ and ‘ti’ as in palatial. Abstract Concerns abound about the state of the world's fisheries, and by association fisheries science and fisheries management. An important question is the cause of the problems with fisheries, which are managed based on advice given by practioners of the discipline of fisheries science. These scientists provide advice in two distinct forms, one ‘policy supporting’ and the other ‘policy forming’. Policy supporting advice is given within an existing management setting and is typically provided only after rigorous and standardized evaluation. In contrast, there is no formal basis for evaluating policy‐forming advice. Criteria for evaluating the adequacy of policy forming advice are difficult to define, and the absence of such criteria poses difficulties for both fisheries scientists and managers. Following a medical practice analogy, we propose rigorously conducting ‘autopsies’ of fisheries as an approach for evaluating policy‐forming advice. A systematic approach to conducting such autopsies is suggested, with the recognition that this may be crucial for the further development of fisheries science as a scientific discipline rather than as an art form.

HISTORICAL OBSERVATIONS OF HUMPBACK AND BLUE WHALES IN THE NORTH ATLANTIC OCEAN: CLUES TO MIGRATORY ROUTES AND POSSIBLY ADDITIONAL FEEDING GROUNDS - Randall R. Reeves; Tim D. Smith; Elizabeth A. Josephson; Phillip J. Clapham; Gillian Woolmer (Marine Mammal Science, 2004)
A bstract The seasonal distributions of humpback and blue whales ( Megaptera novaeangliae and Balaenoptera musculus , respectively) in the North Atlantic Ocean are not fully understood. Although humpbacks have been studied intensively in nearshore or coastal feeding and breeding areas, their migratory movements between these areas have been largely inferred. Blue whales have only been studied intensively along the north shore of the Gulf of St. Lawrence, and their seasonal occurrence and movements elsewhere in the North Atlantic are poorly known. We investigated the historical seasonal distributions of these two species using sighting and catch data extracted from American 18th and 19th century whaling logbooks. These data suggest that humpback whales migrated seasonally from low‐latitude calving/ breeding grounds over a protracted period, and that some of them traveled far offshore rather than following coastal routes. Also, at least some humpbacks apparently fed early in the summer west of the Mid‐Atlantic Ridge, well south of their known present‐day feeding grounds. In assessing the present status of the North Atlantic humpback population, it will be important to determine whether such offshore feeding does in fact occur. Blue whales were present across the southern half of the North Atlantic during the autumn and winter months, and farther north in spring and summer, but we had too few data points to support inferences about these whales' migratory timing and routes.

MEASUREMENT OF PHOTOGRAPHIC QUALITY AND INDIVIDUAL DISTINCTIVENESS FOR THE PHOTOGRAPHIC IDENTIFICATION OF HUMPBACK WHALES, MEGAPTERA NOVAEANGLIAE - Nancy Friday; Tim D. Smith; Peter T. Stevick; Judy Allen (Marine Mammal Science, 2000)
A bstract Accurate identification of humpback whales from photographic identification data depends on the quality of the photographs and the distinctiveness of the flukes. Criteria for evaluating photographic quality and individual distinctiveness were developed involving judgments about overall quality or distinctiveness and about specific aspects of each. These criteria were tested for the level of agreement among judges. The distinctiveness scheme was tested for the independence of distinctiveness judgments and photographic quality. Our results show that judges could agree when evaluating specific and overall aspects of photographic quality and individual distinctiveness. The level of agreement varied for different pairs of judges, and less adept judges were identified. Ability to agree on evaluations of photographic quality was independent of the experience of the judges. Overall photographic quality and overall distinctiveness were successfully predicted from more specific variables, but the agreement between judges for these was not significantly greater than the agreement for the overall measures judged directly. There was no correlation between individual distinctiveness and photographic quality for four of the five judges, but the power of this rest may be low. Analyses of photographic identification data frequently require evaluations of photographic quality and individual distinctiveness. To obtain reliable results from such analyses, evaluation schemes and judges should be tested to ensure reliable and consistent evaluations.

“Simultaneous and Complementary Advances”: Mid-century Expectations of the Interaction of Fisheries Science and Management - Tim D. Smith (Reviews in Fish Biology and Fisheries, 1998)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)